Integrated promoter-capture Hi-C and Hi-C analysis reveals fine-tuned regulation of the 3D chromatin architecture in colorectal cancer - Saw, Ajay Kumar; Madhok, Ayush; Bhattacharya, Anupam; Nandi, Soumyadeep; Galande, Sanjeev (Frontiers in Genetics, 2025)
Introduction:Hi-C is a widely used technique for mapping chromosomal interactions within a 3D genomic framework, however, its resolution is often constrained by sequencing depth, making it challenging to detect fine-scale interactions. To overcome this limitation, Promoter-Capture Hi-C (PCHi-C), as it selectively enriches for promoter-associated interactions, was employed. This study integrates PCHi-C and Hi-C datasets from colorectal cancer (CRC) models investigate chromosomal interaction dynamics across various regulatory levels, from cis-regulatory elements to topologically associated domains (TADs). The primary goal is to examine how genomic structural alterations shape the epigenomic landscape in CRC and to assess their potential role in colorectal cancer susceptibility.Methods:PCHi-C and Hi-C datasets from multiple colorectal cancer (CRC) studies were integrated to enhance the resolution of chromatin interaction mapping. The analysis focused on identifying fine-scale interactions within topologically associated domains (TADs) while incorporating histone modification landscapes (H3K27ac, H3K4me3) and transcriptomic signatures from CRC cell lines and the TCGA database. For experimental validation, ChIP-quantitative PCR was performed at the promoters of target genes using the highly malignant colorectal cell line HT29 and compared it to an embryonic cell line NT2D1.Results:Our integrated analysis revealed significant genomic structural instability in CRC cells, closely associated with tumor-suppressive transcriptional programs. We identified nine dysregulated genes, including long non-coding RNAs (MALAT1, NEAT1, FTX, and PVT1), small nucleolar RNAs (SNORA26 and SNORA71A), and protein-coding genes (TMPRSS11D, TSPEAR, and DSG4), all of which exhibited a substantial increase in expression in CRC cell lines compared to human embryonic stem cells (hESCs). Additionally, we observed enriched activation-associated histone modifications (H3K27ac and H3K4me3) at the potential enhancer regions of these genes, indicating possible transcriptional activation. ChIP-quantitative PCRs conducted using in the highly malignant CRC cell line HT29, compared to the embryonic cell line NT2D1, further validated these findings, reinforcing the link between altered chromosomal interactions and gene dysregulation in CRC.Discussion:This study sheds light on the dynamic 3D genome organization in CRC, highlighting critical structural changes associated with disease-associated loci. The identification of nine dysregulated genes points to potential biomarkers for colorectal cancer, with implications for diagnostic and therapeutic strategies. The combination of Hi-C and PCHi-C offers a refined approach for detecting chromosomal interactions at a higher resolution, laying the foundation for future studies on cancer-associated chromatin architecture.